Teaching quality assurance of Chinese-foreign cooperation education in provincial universities in Western China / Hou Yanfang and Rohayati Mohd Isa - Yanfang, Hou; Mohd Isa, Rohayati (Universiti Teknologi MARA, 2024)
This research is dedicated to examining and assessing the mechanisms employed in ensuring and managing teaching quality within Chinese-Foreign Cooperative Education (CFCE) universities situated in the western provinces of China. The study particularly aims to delve into and scrutinize the influencing factors affecting the internal teaching quality of CFCE, including the construction of the teaching staff, the quality of student resource, teaching conditions, and teaching management. Given the perceived weaknesses in these aspects, the establishment of a sound teaching quality assurance system is posited as an instrument in enhancing CFCE's outcomes, ultimately facilitating the attainment of desired results and fostering Chinese-foreign cultural exchange. The study methodology used is qualitative, utilizing a semi-structured interview approach. The selection of research samples, comprising interview participants, was conducted at three CFCE universities in Shaanxi, which serves as a representative western province in China. The investigation endeavors to elucidate the challenges, strategies, and outcomes associated with teaching quality assurance within CFCE. The research findings not only shed light on the influencing factors but also propose strategies that pivot around the student-oriented concept. Additionally, the incorporation of high-quality foreign educational resources and the adoption of scientific evaluation methods are recommended strategies. These approaches aim to improve the teaching quality of CFCE, contributing to the growth and success of students and advancing the high-quality and sustainable development of CFCE